2005
DOI: 10.1152/jn.00685.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model of the Octopus Arm. II. Control of Reaching Movements

Abstract: The dynamic model of the octopus arm described in the first paper of this 2-part series was used here to investigate the neural strategies used for controlling the reaching movements of the octopus arm. These are stereotypical extension movements used to reach toward an object. In the dynamic model, sending a simple propagating neural activation signal to contract all muscles along the arm produced an arm extension with kinematic properties similar to those of natural movements. Control of only 2 parameters fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…Although the nervous control of locomotion is poorly understood, these single-arm movements do not necessarily require complex control. Nervous control of reaching is decentralized and can proceed without involvement of the brain's motor control region [the peduncle lobe (Messenger, 1967;Williamson and Chrachri, 2004)], allowing for simple feed-forward movements capable of incorporating feedback (Gutfreund et al, 1996;Gutfreund et al, 1998;Matzner et al, 2000;Sumbre et al, 2001;Yekutieli et al, 2005a;Yekutieli et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Although the nervous control of locomotion is poorly understood, these single-arm movements do not necessarily require complex control. Nervous control of reaching is decentralized and can proceed without involvement of the brain's motor control region [the peduncle lobe (Messenger, 1967;Williamson and Chrachri, 2004)], allowing for simple feed-forward movements capable of incorporating feedback (Gutfreund et al, 1996;Gutfreund et al, 1998;Matzner et al, 2000;Sumbre et al, 2001;Yekutieli et al, 2005a;Yekutieli et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated this behaviour by directly extracting the muscle contraction patterns from live octopus and externally applying these patterns to several octopus arm models. [30][31][32] It was then observed that the body dynamics may be used to control the arm's motion in a closed-loop manner by embedding nonlinear limit cycles. 8 However, the final step of bridging the gap between these findings and a robotic application was missing in previous works.…”
Section: Octopus Nervous Systemmentioning
confidence: 99%
“…Aside from integrating preprocessed visual input from the visual system, the relatively small CNS controls the highly autonomous PNS. The CNS has been shown to only send movement initiation signals to the PNS [24]. The PNS takes a large part of motor control function by embedded local motor programs [25].…”
Section: Nervous Systemsmentioning
confidence: 99%